Career Adaptability and Unemployment Anxiety in Turkish Senior Undergraduate Students: The Mediating Role of Career Stress - Demi̇rtaş, Ayşe Sibel; Kara, Ahmet (Turkish Psychological Counseling and Guidance Journal, 2022)
The purpose of this study is to reveal the mediating role of career stress in the relationship between career adaptability and unemployment anxiety. A total of 410 senior undergraduate students, 308 females (73.7%) and 110 males (26.3%), participated in this study. The ages of the participants ranged from 18 to 36 years with a mean age of 22.25 (SD:1.87). The data were collected using the Personal Information Form, the Career Adaptability Scale, the Career Stress Scale, and the Unemployment Anxiety Scale. The fit of the model was assessed using the path analysis technique. Also, the bootstrapping analysis was performed to provide evidence for the significance of the mediating effect in the model. The findings of the research confirmed that career uncertainty and lack of information partially mediated the relationship between career discovery and unemployment anxiety. Furthermore, the findings revealed that career uncertainty, lack of information, and pressure of finding a job fully mediated the relationship between career plan and unemployment anxiety. The results were discussed in the framework of the literature and the recommendations were proposed.
Keywords: Psikoloji; Psychology; Career Adaptability; Career Stress; Unemployment Anxiety; 4. Education; 8. Economic growth